Rapid Mapping of Hydrological Systems in Tanzania Using a Towed Transient Electromagnetic System. Issue 1 (15th September 2021) - Grombacher, Denys; Maurya, Pradip Kumar; Lind, Johan Christensen; Lane, John; Auken, Esben
Abstract: Limited knowledge of local groundwater systems often results in the failure of boreholes to yield water of the required quantity and quality. This is particularly problematic in the developing world, where financial resources are often limited, and failed wells represent a significant financial burden. To enhance understanding of local hydrological systems, noninvasive geophysical methods can aid the understanding of hydrogeological structures and identification of groundwater sources needed to optimize siting of wells. Here, we highlight the utility of a relatively new towed‐transient electromagnetic system, called tTEM. This system is a rapidly deployable mobile geophysical method well‐suited to cost‐efficient characterization of local‐to‐regional groundwater systems. Results from tTEM surveys conducted in two refugee camps and several host communities in western Tanzania demonstrate the capability of the method to characterize shallow aquifer systems with high lateral and vertical resolution, with data collection typically exceeding 15 to 20 line‐kilometers (km) per day. This work focuses on tTEM's ability to provide semiquantitative insights into regional hydrogeological settings when supporting data required for more rigorous interpretation/modeling is lacking. The system provided useful data within communities with low density of electrification and near buildings with metal roofs and walls. tTEM‐derived resistivity profiles were correlated with limited local borehole lithologic information to develop conceptual models of the local groundwater systems. These models were used to successfully guide the siting of a production well and to identify future drilling targets in the refugee camps and surrounding communities. Abstract : Article impact statement : The value of a towed transient electromagnetic system for optimized well‐siting is highlighted in a campaign in rural Tanzania.